High ten‐year remission rates following rituximab, fludarabine, mitoxantrone and dexamethasone (R‐FND) with interferon maintenance in indolent lymphoma: Results of a randomized Study. (24th March 2017) - Nastoupil, Loretta J.; McLaughlin, Peter; Feng, Lei; Neelapu, Sattva S.; Samaniego, Felipe; Hagemeister, Fredrick B.; Ayala, Ana; Romaguera, Jorge E.; Goy, Andre H.; Neal, Eleanor; Wang, Michael; Fayad, Luis; et al.
Summary: We report a single‐centre, randomized study evaluating the efficacy and safety of concurrent fludarabine, mitoxantrone, dexamethasone (FND) and rituximab versus sequential FND followed by rituximab in 158 patients with advanced stage, previously untreated indolent lymphoma, enrolled between 1997 and 2002. Patients were randomized to 6–8 cycles of FND followed by 6 monthly doses of rituximab or 6 doses of rituximab given concurrently with FND. All patients who achieved at least a partial response received 12 months of interferon (IFN) maintenance. Median ages were 54 and 55 years. The two groups were comparable with the exception of a higher percentage of females (65% vs. 43%) and baseline anaemia (23% vs. 11%) in the FND followed by rituximab group. Complete response/unconfirmed complete response rates were 89% and 93%. The most frequent grade ≥ 3 toxicity was neutropenia (86% vs. 96%). Neutropenic fever occurred in 21% and 16%. Late toxicity included myelodysplastic syndrome ( n  = 3) and acute myeloid leukaemia ( n  = 5). With 12·5 years of follow‐up, no significant differences based on treatment schedule were observed. 10‐year overall survival estimates were 76% and 73%. 10‐year progression‐free survival estimates were 52% and 51%. FND with concurrent or sequential rituximab, and IFN maintenance in indolent lymphoma demonstrated high response rates and robust survival.